A Case study: Nitrate in Processed Meat Products sold in Convenient Stores and Supermarkets in Bangkok, Thailand - Pawanrat Dechbamrung; Nattapat Withayamongkol; Pinyada Ngamcherdchoosit; Waralee Tingpattana; Warintorn Yodcharoen; Patitta Promliponkul; Suppanuch Nuchprayoon (Zenodo (CERN European Organization for Nuclear Research), 2022)
Abstract: Background: Currently Nitrate is a food preservative that is used in processed meat products for longer shelf life, and causes desirable color and odor of the products. Objectives: The objective of this study is to investigate the contamination of Nitrate that exceeds standards in the western processed meat products from convenient stores and supermarkets. Methods: The study collected 17 western processed meat product samples in June 2022 from convenient stores and supermarkets in Bangkok, Thailand and investigated the contamination of Nitrate with GT-Nitrate test kit. Results: There was 17.65% of the samples which was not met the Nitrate exceeded standard value according to the regulations on the usage of food additives, the Notification of Ministry of Public Health number 389 in B.E. 2561 (2018), Re; food additives (number 5) determine to use Nitrate exceed than 500 mg. per kg. The 2 samples of ham products (50%) had the highest amount of Nitrate contamination that did not meet the standards also, followed by 1 sample of sausage product (16.67%). In addition, the bacon and bologna products were not found to have Nitrate contamination that exceeded standard value. Conclusions: This study showed that we found a few of western processed meat products in convenient stores and supermarkets which were contaminated with Nitrate, it demonstrated that there is still used Nitrate by over the standard generally. Keywords: Nitrate, Nitrite, western processed meat products. Title: A Case study: Nitrate in Processed Meat Products sold in Convenient Stores and Supermarkets in Bangkok, Thailand Author: Pawanrat Dechbamrung, Nattapat Withayamongkol, Pinyada Ngamcherdchoosit, Waralee Tingpattana, Warintorn Yodcharoen, Patitta Promliponkul, Suppanuch Nuchprayoon International Journal of Healthcare Sciences ISSN 2348-5728 (Online) Vol. 10, Issue 1, April 2022 - September 2022 Page No: 246-250 Research Publish Journals Website: www.researchpublish.com Published Date: 27-August-2022 DOI: https://doi.org/10.5281/zenodo.7027329 Paper Download Link (Sources) https://www.researchpublish.com/papers/a-case-study-nitrate-in-processed-meat-products-sold-in-convenient-stores-and-supermarkets-in-bangkok-thailand
Keywords: Nutritional Studies and Diet; Food Waste Reduction and Sustainability